Analysis of Process Quality in the Weaving Section Using Failure Mode and Effect Analysis and Fault Tree Analysis: A Case Study of PT XYZ - Atikasari, Dilla Fajar; Yun, Yun (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the main causes of warp-jump defects in gray fabric production at PT XYZ using Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA). This analysis identified two main causes: decreased machine performance and operator fatigue. The FMEA results indicate that these factors contribute significantly to product defects, with machine performance having the highest Risk Priority Number (RPN). This study suggests that routine machine maintenance and improved workforce management through closer training and supervision are crucial to reducing defects and increasing operational efficiency.